2022
DOI: 10.3389/fphar.2022.982424
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of IDH1 mutant inhibitor in cancer therapy

Abstract: Isocitrate dehydrogenase (IDH) is the key metabolic enzyme that catalyzes the conversion of isocitrate to α-ketoglutarate (α-KG). Two main types of IDH1 and IDH2 are present in humans. In recent years, mutations in IDH have been observed in several tumors, including glioma, acute myeloid leukemia, and chondrosarcoma. Among them, the frequency of IDH1 mutations is higher than IDH2. IDH1 mutations have been shown to increase the conversion of α-KG to 2-hydroxyglutarate (2-HG). IDH1 mutation-mediated accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…To date, numerous mIDH-selective inhibitors have been developed, and some of them have been shown to effectively reduce 2-HG production in preclinical tumor models and/or in patients [ 4 , 46 , 47 ]. As will be described in more detail in Section 7 , almost all of them effectively inhibit the predominant IDH1 R132H mutation and many classes also target additional mutations, which could be advantageous for imaging in glioma patients with non-canonical mutations.…”
Section: Considerations For the Development Of Midh-selective Pet-tra...mentioning
confidence: 99%
“…To date, numerous mIDH-selective inhibitors have been developed, and some of them have been shown to effectively reduce 2-HG production in preclinical tumor models and/or in patients [ 4 , 46 , 47 ]. As will be described in more detail in Section 7 , almost all of them effectively inhibit the predominant IDH1 R132H mutation and many classes also target additional mutations, which could be advantageous for imaging in glioma patients with non-canonical mutations.…”
Section: Considerations For the Development Of Midh-selective Pet-tra...mentioning
confidence: 99%
“…While this agent improves clinical outcomes, patients ultimately relapse. 16 Wu developed the first genetically engineered mouse model for mIDH1 ICC to understand the impacts of mIDH1 inhibition and identify strategies to improve its efficacy. He showed that the predominant IDH1 mutant allele in cholangiocarcinoma produces higher levels of R-2HG than the allele commonly found in glioblastoma.…”
Section: Importance Of T Cells In Targeting Midh1 In Cholangiocarcinomamentioning
confidence: 99%
“…The mIDH1 inhibitor ivosidenib was approved for mIDH1 advanced or metastatic cholangiocarcinoma in 2021. While this agent improves clinical outcomes, patients ultimately relapse 16 . Wu developed the first genetically engineered mouse model for mIDH1 ICC to understand the impacts of mIDH1 inhibition and identify strategies to improve its efficacy.…”
Section: Metabolic Regulation Of the Anticancer Immune Responsementioning
confidence: 99%
“…Of the 21 patients, 11 individuals (52%) achieved stable disease during the study [77]. There are multiple other IDH-targeted therapies in development [184]. In a phase II trial, the compound AG-120 is tested in patients with chondrosarcoma mutant IDH1.…”
Section: Targeted Treatmentmentioning
confidence: 99%